VALIDASI MODUL BERMAIN PERAN âAKU SAYANG KAWANâ UNTUK MENINGKATKAN PENGETAHUAN TENTANG PERILAKU PROSOSIAL PADA ANAK USIA DINI - , SITA ALFIYAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In social relationship, early age children have been able to show a prosocial behavior. However, there are some early age children who have not performed this social behavior, for example helping their friends who have difficult problem or sharing their foods. Prosocial behavior is developed by firstly embedding knowledge in the early age children. The aim of this research is to carry out the validation of role play module âAku Sayang Kawanâ to improve the knowledge of prosocial behavior in the early age children. The hypothesis of this research was that the role playing module âAku Sayang Kawanâ could improve the knowledge of prosocial behavior in the early age children. The method of this research was the untreated control group design with dependent pretest and post test sample design experiment. The participants of this research were separated into control group (13 children) and experiment group (11 children). The result of statistical test using anova mixed design was the score F =27,20 (p<0,01). It means that there was significantly different knowledge score of prosocial behavior from pretest to post-test between experiment and control groups. The role play module âAku Sayang Kawanâ could be applied to improve the knowledge of prosocial behavior in the early age children.